PSC-derived intestinal organoids with apical-out orientation as a tool to study nutrient uptake, drug absorption and metabolism - Kakni, Panagiota; López-Iglesias, Carmen; Truckenmüller, Roman; Habibović, Pamela; Giselbrecht, Stefan (Frontiers in Molecular Biosciences, 2023)
Intestinal organoids recapitulate many features of the in vivo gastrointestinal tract and have revolutionized in vitro studies of intestinal function and disease. However, the restricted accessibility of the apical surface of the organoids facing the central lumen (apical-in) limits studies related to nutrient uptake and drug absorption and metabolism. Here, we demonstrate that pluripotent stem cell (PSC)-derived intestinal organoids with reversed epithelial polarity (apical-out) can successfully recapitulate tissue-specific functions. In particular, these apical-out organoids show strong epithelial barrier formation with all the major junctional complexes, nutrient transport and active lipid metabolism. Furthermore, the organoids express drug-metabolizing enzymes and relevant apical and basolateral transporters. The scalable and robust generation of functional, apical-out intestinal organoids lays the foundation for a completely new range of organoid-based high-throughput/high-content in vitro applications in the fields of nutrition, metabolism and drug discovery.